Illuminating the benefits and limitations of forensic light sources. Issue 1 (January 2023) - Finnis, Jonathan; Davidson, Geraldine; Fraser, Isla; Murphy, Charlotte; Hargreaves, Charlotte; Stevenson, Nighean; Doole, Sharon; Rogers, Carol
Abstract: Forensic light sources, such as a Crime-lite, are used in forensic laboratories and by police staff in the examination for, and detection of, biological material. Whilst the benefits of using forensic light sources are relatively well understood, their limitations are less-so. This report details the outcome of studies, validation and review by three forensic laboratories, as well as three case examples, to highlight both the strengths and weaknesses of the tested forensic light sources and to demonstrate that, whilst a useful preliminary screening tool, they should not be used in isolation without subsequent presumptive chemical testing. False positives and negatives are common, and the background substrate and specific biological material present can have a significant effect on the outcome of examination when using a forensic light source.